The Effect of Line Configuration on Lightning-Induced Voltages on Overhead Conducting Lines (2012)
Lightning-Induced Voltages (LIV) affect all electrical conductors and could damage electronic circuits and gadgets even without applied voltage. Several factors, including electrical power line configuration, can affect the magnitude of the lightning-induced voltages. Previous research paid less attention to the effect of line configuration on lightning-induced voltages on overhead power lines and other lines in the tropical environment. The effect of line configuration of electrical lines (with and without earth-wires) on lightning-induced voltages on overhead power lines in tropical environment was investigated. Six lightning channel models: transmission line; modified transmission line with linear decay; modified transmission line with exponential decay; Bruce-Golde; traveling current source; and Linearly Rising Current with Constant Tail (LRCCT) were used to reproduce the following lightning parameters: return-stroke peak current, Ip ; specific velocity, β and front duration, tf . The one that duplicated the condition in tropical environment was used to investigate the LIV on power lines of different line configurations: Vertical Profile With Earth-wire (VPWE) above topmost conductor and below lowest; Vertical Profile Without Earth-wire (VPWOE); Horizontal Profile With Two Earth-wires (HPWTE) symmetrically placed above and below conductors; and Horizontal Profile Without Earth-wires (HPWOE). The resulting partial differential equations from the interaction of lightning current with electrical lines were derived from Green‟s function and solved using the Laplace transform technique. From this, a C-sharp application programme interface was developed with input values of lightning parameters. Output of the programme was induced-voltage as function of time. The Peak Induced-Voltage (PIV) was identified from the plot of induced voltage - time graph. The PIV for HPWOE was validated with available experimental data. For each configuration the Protective Ratios (PR) were determined. Only the LRCCT model duplicated the condition in tropical environment satisfactorily. The PIV increased linearly with Ip , but decreased exponentially with β and tf. The PIV on lowest, middle and topmost conductors were 11.6 x 103 V, 13.7 x 103 V and 15.7 x 103 V respectively for VPWOE. The corresponding values for VPWE above topmost conductor were 10.5 x 103 V, 12.1 x 103 V and 13.0 x 103 V; while VPWE below lowest conductor had values 10.0 x 103 V, 12.7 x 103 V and 15.0 x 103 V. The PR for lowest, middle and topmost conductors were 0.91, 0.89 and 0.83 respectively for VPWE above topmost conductor. The PIV values of middle conductor and each of the outer conductors were 9.4 x 103 V and 8.7 x 103 V respectively for HPWOE; compared with an experimental value of 8.7 x 103 V. Above the line conductors, corresponding PIV values were 6.9 x 103 V and 7.1 x 103 V; while below the line conductors were 7.5 x 103 V and 7.2 x 103 V for HPWTE. The PR of the middle conductor and each of the outer conductors were 0.73 and 0.8 respectively for HPWTE above conductors. The PIV values dropped by a minimum of 25.0% when the lines carried current for all line configurations. Line configuration influenced the lightning-induced voltages of which magnitude was reduced by earth-wires. The horizontal profile with two earth-wires symmetrically placed above the conductors may be preferred to the vertical profile with earth-wire above topmost conductor.